No slurping, no burping! : a tale of table manners - LaReau, Kara; Bové, Lorelay (New York : Disney * Hyperion Books, 2014)
Evie and Simon always mind their manners, but their father has a lot to learn before a surprise dinner guest arrives.
Keywords: Etiquette -- Fiction; Dinners and dining -- Fiction; Fathers -- Fiction; Humorous fiction